Historical Records Fail to Support Agent Orange Exposure of Veterans Stationed in Thailand - Young, Alvin Lee (Advances in Social Sciences Research Journal, 2023)
In the case of Thailand and its many airbases, the Compensation Service of the United States Department of Veterans Affairs has not conducted a comprehensive search of the historical records that were retrieved from Vietnam and are now a continuing source of research. Thailand veterans were previously eligible for health care for any injuries they incurred during their service in Thailand. However, they were not eligible for health care for diseases and compensation as provided to Vietnam veterans under the Agent Orange Act of 1991. Recently, the “Promise to Address Comprehensive Toxics Act” (PACT Act) was passed by the United States Congress that permits veterans who served in Thailand and Guam during the Vietnam War to be eligible for health care and compensation for their exposure to Agent Orange, despite the absence of any evidence from historical records. Too often the pressure from members of Congress, as in the case of Thailand and Guam, the enactment of the PACT Act dictated a course of action. This action and others involving Agent Orange are examples where “political” forces make a mockery of the science and historical records.